2002
DOI: 10.1161/01.cir.0000042675.59901.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of “Benign” Mutations in the β-Myosin Heavy Chain, Cardiac Troponin T, and α-Tropomyosin Genes in Hypertrophic Cardiomyopathy

Abstract: Background-Genotype-phenotype correlative studies have implicated 8 particular mutations that cause hypertrophic cardiomyopathy (HCM) as "benign defects," associated with near-normal survival: N232S, G256E, F513C, V606M, R719Q, and L908V of ␤-myosin heavy chain (MYH7); S179F of troponin T (TNNT2); and D175N of ␣-tropomyosin (TPM1). Routine genetic screening of HCM patients for specific mutations is anticipated to provide important diagnostic and prognostic information. The frequency and associated phenotype of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(84 citation statements)
references
References 38 publications
1
77
1
5
Order By: Relevance
“…This is consistent with our previous studies, which demonstrated that the presence or absence of specific HCM mutations previously annotated as "malignant" or "benign" should not be used for prognosis or risk stratification. 27,28 From our previous studies, it also seems that the phenotype may not be a reliable predictor of the specific causative mutation. 27,28 In the subgroup of individuals harboring thin filament defects (nϭ18), no statistical difference was evident when compared with the rest of the cohort.…”
Section: Phenotype Of Patients With Thin Filament Hcmmentioning
confidence: 98%
See 1 more Smart Citation
“…This is consistent with our previous studies, which demonstrated that the presence or absence of specific HCM mutations previously annotated as "malignant" or "benign" should not be used for prognosis or risk stratification. 27,28 From our previous studies, it also seems that the phenotype may not be a reliable predictor of the specific causative mutation. 27,28 In the subgroup of individuals harboring thin filament defects (nϭ18), no statistical difference was evident when compared with the rest of the cohort.…”
Section: Phenotype Of Patients With Thin Filament Hcmmentioning
confidence: 98%
“…27,28 From our previous studies, it also seems that the phenotype may not be a reliable predictor of the specific causative mutation. 27,28 In the subgroup of individuals harboring thin filament defects (nϭ18), no statistical difference was evident when compared with the rest of the cohort. Our findings suggest that individuals with thin filament mutations had a similar degree of hypertrophy, age at presentation, and incidence of a family history of SCD as those without such mutations.…”
Section: Phenotype Of Patients With Thin Filament Hcmmentioning
confidence: 98%
“…Mutation analysis for the purpose of risk stratification of sudden death, although prominently portrayed in the subspecialty literature, [1][2][3][4][7][8][9][10][11][12]16,[55][56][57][58][59][60][61][62][63][64][65][66][67] has limited practical impact on the present considerations. First, the diagnostic strategy of DNA analysis is time consuming, expensive, and limited to a small number of highly specialized research-oriented laboratories 1,2,8,64 -67 and thus is not yet routinely available to the practicing clinician for the purpose of patient management and formulation of exercise recommendations.…”
Section: Role Of Genetic Analysismentioning
confidence: 99%
“…Some of the TNNT2 mutations were associated with an adverse prognosis, and this raised the possibility that the identification of mutations in this gene may identify individuals at high risk of SCD, who would benefit from the implantation of a cardioverter defibrillator. Because some of the TNNT2 mutations have been associated with a high incidence of SCD in spite of minimal hypertrophy, the analysis of this gene could be of special interest in asymptomatic individuals with a family history of SCD (22,(24)(25)(26).…”
Section: © 2003 American Association For Clinical Chemistrymentioning
confidence: 99%